Image steganalysis: real-time adaptive colour image segmentation for hidden message retrieval and Matthew's correlation coefficient calculation. (24th February 2022) - Yamini, B.; Sabitha, R.
Adaptive image steganography is the method of hiding secret information in colour adaptive regions of the image. Its counter method to reveal hidden secret information is called as adaptive image steganalysis. In the proposed method, the colour correlations between pixels are used to identify the adaptive region of the image by real time adaptive colour image segmentation. Bi-cubic interpolation method is applied on these colour adaptive regions to extract the features from the selected region. These features are considered for classification using support vector machine classifier, to distinguish between stego and cover images. Reversible two least significant bit (LSB) technique is used to identify and to retrieve the hidden content from the payload locations. The accuracy is measured using Matthew's correlation coefficient calculation. The results of real-time adaptive colour image segmentation outperform the methods, normalised cut segmentation, MX-quadtree segmentation and watershed segmentation.